Schitt's Creek Season 5 - Levy, Eugene, 1946-; O'Hara, Catherine, 1954-; Levy, Daniel, 1983-; Murphy, Annie, 1986-; Robertson, Jennifer, 1971-; Hampshire, Emily, 1981-; Rozon, Tim.; Levy, Sarah, 1986-; Elliott, Chris, 1960- (Australia Acorn Media, 2017)
Nominated for four Emmy Awards in 2019, Schitt's Creek is a smash hit with critics and audiences alike. Created by and starring Eugene Levy and Daniel Levy, this irreverent and original character-driven comedy centres on the 'reversal of fortune' story of the once filth-rich Rose family. Suddenly finding themselves broke, the Roses are forced to rebuild their empire in Schitt's Creek, a small town they once purchased as a joke. As the series go on, we see the family thrive in a place they begin to call home, ready to take their personal relationships, business pursuits and, for some, exit strategies to the next level.
Eugene Levy, Catherine O'Hara, Daniel Levy, Annie Murphy, Jennifer Robertson, Emily Hampshire, Tim Rozon, Sarah Levy, Chris Elliott.
Widescreen 16:9.
In English.
113735
Keywords: Bankruptcy -- Drama; Actors -- Drama; Rich people -- Drama; Poverty -- Drama; Small cities -- Drama; Comedy -- Video recordings; Television comedies; Drama; Video recordings